Creative Writing Among Chinese Teachers: An Overview of Phenomenological Psychology - Anas Ahmadi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research is a descriptive study that wants to explore creative writing among Chinese teachers through the perspective of phenomenological psychology. The method used in this research is qualitative. The respondents of this study were 19 teachers who came from formal school teachers and LBB teachers. Data collection techniques were carried out by means of questionnaires, documentation, and interviews. Data analysis technique is done by identification, classification, and reduction. The researcher also carried out data validity so that the data was maintained scientifically. The results of the study show the following. First, most Chinese teachers do not write creatively because they are more concerned with the field of Mandarin. Second, from the aspect of the cause of the lack of creative writing in Chinese teachers who occupy the highest position is the environment because in the opinion of respondents, the environment is very influential because in their daily life they live in an environment.